2020
DOI: 10.1155/2020/2974268
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology to Uncover the Biological Basis of Spleen Qi Deficiency Syndrome and Herbal Treatment

Abstract: Spleen qi deficiency (SQD) syndrome is one of the basic traditional Chinese medicine (TCM) syndromes related to various diseases including chronic inflammation and hypertension and guides the use of many herbal formulae. However, the biological basis of SQD syndrome has not been clearly elucidated due to the lack of appropriate methodologies. Here, we propose a network pharmacology strategy integrating computational, clinical, and experimental investigation to study the biological basis of SQD syndrome. From c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…In recent years, there has been increasing concern about the application of bioinformatics and systems biology approaches to understand the development of diseases and the mechanism of the TCMs ( Li and Zhang, 2013 ; Zheng et al, 2018 ; Tan et al, 2019 ; Wang X. et al, 2020 ). Based on the new trend in interdisciplinary fields, Li et al established TCM systems bioinformatics (TCMSB) and proposed for the first time a map of “Phenotype network-Biological network-Herb network,” which contributes to identifying network biomarkers for TCM syndrome and herb formula ( Li et al, 2007 ; Li, 2009 ).…”
Section: The Classification and Treatment Of Cold And Hot Syndromesmentioning
confidence: 99%
“…In recent years, there has been increasing concern about the application of bioinformatics and systems biology approaches to understand the development of diseases and the mechanism of the TCMs ( Li and Zhang, 2013 ; Zheng et al, 2018 ; Tan et al, 2019 ; Wang X. et al, 2020 ). Based on the new trend in interdisciplinary fields, Li et al established TCM systems bioinformatics (TCMSB) and proposed for the first time a map of “Phenotype network-Biological network-Herb network,” which contributes to identifying network biomarkers for TCM syndrome and herb formula ( Li et al, 2007 ; Li, 2009 ).…”
Section: The Classification and Treatment Of Cold And Hot Syndromesmentioning
confidence: 99%
“…Network pharmacology is an interdisciplinary subject that integrates biological networks, analyzes the relationship between drugs and nodes or network modules, and accelerates the identification of drug targets and the discovery of new biomarkers (Kibble et al, 2015). Our understanding of the biological basis of TCM treatment can be attributed to network pharmacology (Wang et al, 2020) A study was performed that used network pharmacology to research the molecular mechanisms of Lian Hua Qing Wen (a mix of 13 herbs) in novel coronavirus disease, and the results showed that its mechanisms are closely related to modulating inflammation, antiviral action, and protecting the lungs (Zheng et al, 2020). Network pharmacology was also applied in identifying the active compounds from Kai-Xin-San, which is a TCM that consists of 1) ginseng (Panax ginseng), 2) snakeroot (Polygala tenuifolia Wild.…”
Section: Novel Strategies Used For Developing New Natural Products Network Pharmacologymentioning
confidence: 99%
“…Network pharmacology is an interdisciplinary subject that integrates biological networks, analyzes the relationship between drugs and nodes or network modules, and accelerates the identification of drug targets and the discovery of new biomarkers ( Kibble et al, 2015 ). Our understanding of the biological basis of TCM treatment can be attributed to network pharmacology ( Wang et al, 2020 )…”
Section: Novel Strategies Used For Developing New Natural Productsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) theory holds that the effects of tonifying middle and replenishing qi are primarily relevant with tonifying spleen-qi (Wang et al. 2020 ). Furthermore, SQD impairs gastrointestinal function and reduces the ability to obtain nutrients, which then leads to the decline in immune function (Shang et al.…”
Section: Introductionmentioning
confidence: 99%